2005
DOI: 10.1111/j.1525-1594.2005.29100.x
|View full text |Cite
|
Sign up to set email alerts
|

Ascending Aorta Outflow Graft Location and Pulsatile Ventricular Assist Provide Optimal Hemodynamic Support in an Adult Mock Circulation

Abstract: Although continuous flow (CF) and pulsatile flow (PF) ventricular assist devices (VADs) are being clinically used, their effects on aortic blood flow, as a measure of overall blood distribution, remain unclear. In acute VAD support animal experiments, our group has described a zone of turbulent mixing in the aortic arch. The objective of this study was to confirm this finding in the controlled setting of an adult mock circulation, simulating ventricular pathophysiologic states (normal and failing ventricle). C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
(29 reference statements)
0
19
0
Order By: Relevance
“…Previous research indicated that for VAD inlet cannulation the left ventricle cannulation configuration would be preferable, as it allows for more blood to be drained into the VAD thus reducing the work of the native ventricle (Tevaearai et al, 2001). The ascending aorta outflow configuration is better suited for outlet cannulation than the descending aorta configuration in maintaining aortic blood flow characteristics (Litwak et al, 2005). Thus in the current simulation for the in parallel VAD connection, the VAD inlet is connected to the left ventricular apex and the outlet to the ascending aorta.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous research indicated that for VAD inlet cannulation the left ventricle cannulation configuration would be preferable, as it allows for more blood to be drained into the VAD thus reducing the work of the native ventricle (Tevaearai et al, 2001). The ascending aorta outflow configuration is better suited for outlet cannulation than the descending aorta configuration in maintaining aortic blood flow characteristics (Litwak et al, 2005). Thus in the current simulation for the in parallel VAD connection, the VAD inlet is connected to the left ventricular apex and the outlet to the ascending aorta.…”
Section: Methodsmentioning
confidence: 98%
“…Litwak et al (2004) examined the effect of constant flow and pulsatile flow VAD support and outflow graft location on aortic flow in an acute calf model. Litwak et al (2005) and Koenig et al (2004) conducted similar research in an adult mock circulation test rig. No differences in mean aortic flow between constant flow and pulsatile flow VADs were observed in their experimental results.…”
Section: Introductionmentioning
confidence: 97%
“…Kar and colleagues [14] reported that LVADs implanted with an outflow-graft anastomosis to the descending aorta have potential drawbacks such as aortic valve fusion and aortic-root flow stagnation that may alter myocardial perfusion. Similarly, in their experimental study, Litwak and colleagues [16] reported that the mean aortic-arch blood flow decreased when the LVAD outflow-graft anastomosis site was the descending aorta versus the ascending aorta. They also reported that although mean aortic-root and carotid-artery flow are independent of the LVAD outflow-graft location, competitive flow between the native heart and the LVAD may result in turbulent mixing or stagnation in the aortic arch if the LVAD outflow-graft anastomosis is located in the descending aorta [16].…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, in their experimental study, Litwak and colleagues [16] reported that the mean aortic-arch blood flow decreased when the LVAD outflow-graft anastomosis site was the descending aorta versus the ascending aorta. They also reported that although mean aortic-root and carotid-artery flow are independent of the LVAD outflow-graft location, competitive flow between the native heart and the LVAD may result in turbulent mixing or stagnation in the aortic arch if the LVAD outflow-graft anastomosis is located in the descending aorta [16]. Therefore, they suggested that anastomosis of the outflow-graft to the ascending aorta may be optimal for a continuous-flow LVAD.…”
Section: Discussionmentioning
confidence: 93%
“…Flexible sacs have been used to create mock ventricles for use in mock circulation loops in previous studies [5,[12][13][14][15][16]. These mock ventricles were hemi-ellipsoid in shape rather than having the shape of a true ventricle, and thus flow patterns experienced in these ventricles are not indicative of the natural heart.…”
Section: Introductionmentioning
confidence: 98%